2021
DOI: 10.1017/s0033291721004906
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic functional connectivity of hippocampal subregions associated with working memory impairment in melancholic depression

Abstract: Background Previous studies have demonstrated structural and functional changes of the hippocampus in patients with major depressive disorder (MDD). However, no studies have analyzed the dynamic functional connectivity (dFC) of hippocampal subregions in melancholic MDD. We aimed to reveal the patterns for dFC variability in hippocampus subregions – including the bilateral rostral and caudal areas and its associations with cognitive impairment in melancholic MDD. Methods Forty-two treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 134 publications
1
12
0
Order By: Relevance
“…While previous studies had linked verbal memory to hippocampal volume, our findings show associations with working memory/executive function, which has also been documented in several previous studies (e.g [80,[82][83][84]). However, our results go beyond these findings, as we demonstrated that these effects are not related to the traditional, descriptive diagnoses, but apply to all patients and healthy controls on a dimensional level.…”
Section: Diagnoses-common Gmv Alterationssupporting
confidence: 89%
“…While previous studies had linked verbal memory to hippocampal volume, our findings show associations with working memory/executive function, which has also been documented in several previous studies (e.g [80,[82][83][84]). However, our results go beyond these findings, as we demonstrated that these effects are not related to the traditional, descriptive diagnoses, but apply to all patients and healthy controls on a dimensional level.…”
Section: Diagnoses-common Gmv Alterationssupporting
confidence: 89%
“…The hippocampus is an important region involved in memory and cognitive function ( 32 ), composed of different subregions interacting with varying areas of the brain, resulting in a neuro-anatomical network of emotion regulation and cognitive processing ( 33 ). For instance, the hippocampal volume of patients with MDD depreciated substantially ( 34 , 35 ) and elevated after electroconvulsive therapy (ECT) relative to HCs ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided the range of the appropriate window length as 10–75 TR, step = 1 TR, and a moderate sliding window length may maximize the statistical power, because it may be an optimal balance between capturing rapidly shifting dynamic relationships (with shorter windows) and achieving reliable estimates of the correlations between regions (with longer windows) 2,64 . Additionally, a sliding window size of 50 TR and a window step of 1 TR has been repeatedly used in previous studies, and they were able to capture the dynamics 65–68 . Therefore, the present study applied a sliding window size of 50 TR and a window step of 1 TR to calculate the dReHo and dFC.…”
Section: Discussionmentioning
confidence: 97%
“…2,64 Additionally, a sliding window size of 50 TR and a window step of 1 TR has been repeatedly used in previous studies, and they were able to capture the dynamics. [65][66][67][68] Therefore, the present study applied…”
Section: Discussionmentioning
confidence: 99%